JA:2021-4. Quantitative Measurement of an Ag Center's Outcomes: The Project Scoring Matrix. Issue 3 (2nd July 2020) - Cramer, Mary E.; Wilson, Fernando; Wendl, Mary; Duysen, Ellen; Rautiainen, Risto
ABSTRACT: Purpose : The presentation explains the Project Scoring Matrix (PSM) instrument that was developed by the Central States Center for Agricultural Safety and Health (CS-CASH). Aspects include the instrument development process, what key outcomes are measured, data sources, PSM outcomes weighting, and ranking criteria. Methods : The PSM took 2 years to develop under the direction of our health economist, Dr. Fernando Wilson, and in collaboration with the evaluation team and CS-CASH leaders. The PSM is an innovative instrument that quantitatively scores and tracks outcomes. Results/Findings : Findings are used for annual program improvements. Longitudinal data will provide the basis for estimating the economic impact of CS-CASH outcomes using Social Return on Investment (SROI) analysis. Practical Application : The PSM has potential for use in other Centers and is consistent with the NIOSH focus on outcomes Evaluation.